Pendampingan Kemampuan Literasi Anak Melalui Pembelajran Fonik - Alisa Hildayanti; Ratna Dewi Ibrahim; Devaron Suardi; Rifki Arip Nugraha (Lembaga Pengembangan Kinerja Dosen, 2023)
Children's literacy skills play a crucial role in their cognitive and academic development. The phonics learning approach has been proven effective in helping children develop good reading and writing skills. This study aims to describe how children's literacy mentoring through phonics learning can improve their reading and writing skills. children's literacy mentoring through phonics learning has a positive impact in improving reading and writing skills. The involvement of teachers and parents is crucial in providing support and motivation to the children. This research provides a deeper look into how the phonics approach can be effectively implemented in an effort to improve children's literacy.